Ataxia with vitamin E deficiency associated with deafness - Kara, Bülent; Üzümcü, Abdullah; Uyguner, Oya; Rosti, Rasim Özgür; Koçbaş, Ayça; Özmen, Meral; Kayserili, Hülya (The Turkish Journal of Pediatrics, 2008)
Ataxia with vitamin E deficiency (AVED) is a rare autosomal recessive disorder, usually with a phenotype resembling Friedreich ataxia, caused by selective impairment of gastrointestinal vitamin E absorption. Vitamin E supplementation improves symptoms and prevents disease progress. In North Africa and Southern Europe, AVED is as common as Friedreich ataxia. There are no reported cases from Turkey. We herein report a 16-year-old Turkish girl with AVED, who was found to have total deletion of the TTPA gene as well as sensorineural deafness, and we present her follow-up data after vitamin E therapy.